Workforce Coordination And Infection Control In Saudi Dental Settings: Contributions From Dentistry, Nursing, And Security Personnel (The Review of Diabetic Studies, 2025)
Infection prevention and control (IPC) in dental settings requires more than clinical competence; it depends on coordinated teamwork across professional roles that jointly manage patient flow, environmental safety, and adherence to standard precautions. In Saudi Arabia, dental services operate under national IPC expectations and dental-specific guidance that emphasize risk assessment, hand hygiene, personal protective equipment (PPE), instrument reprocessing, environmental cleaning, and safe patient management. This paper examines how workforce coordination among dentists/dental auxiliaries, nursing staff, and security personnel shapes IPC performance in Saudi dental clinics and hospitals. Drawing on a narrative synthesis of authoritative IPC sources and Saudi dental IPC manuals, the paper develops a role-based coordination framework that links clinical workflows (chairside care, aerosol-generating procedures, sterilization, and waste handling) with non-clinical control points (entry screening, crowd management, access control, and visitor policy enforcement). The analysis highlights that IPC breakdowns frequently emerge at “handoff zones” (reception-to-triage, triage-to-operatory, operatory-to-sterile processing, and discharge), where responsibilities overlap or become ambiguous. Nursing staff function as operational integrators—supporting triage, surveillance, patient education, and compliance monitoring—while security personnel contribute by enforcing controlled access, supporting respiratory-illness screening pathways, protecting restricted sterile areas, and assisting incident response. The paper proposes measurable coordination mechanisms: structured briefings, zoning and signage, audit-and-feedback loops, competency-based training, and incident command alignment during outbreaks. Recommendations focus on clarifying role boundaries, standardizing cross-role communication, strengthening training for non-clinical staff in IPC-relevant tasks, and embedding security personnel within IPC governance without expanding them into clinical roles.